Production technology of beverages enriched with natural vegetable ingredients with adaptogenic properties - L. G. Vlashchik; A. V. Tarasenko (Новые технологии)
The problem of the production of enriched drinks from natural plant materials for preventive purposes is considered. Pectin extract from grape processing products is an enriching component in beverage technology.  The studies were carried out in accordance with the innovative directions of development of the food and processing industry formulated in the Strategy of the scientific and technological development of the Russian Federation until 2030.  One of the tasks of scientific and technological development of the food industry considered in the research is to increase consumer demand for fortified foods, healthy and functional foods, which necessitates the development of food technologies that enhance protective functions of the body to prevent nutritional-dependent diseases. The idea is substantiated that the most technologically advanced way of creating food products with preventive properties is the technology of drinks with high biological value.  Information is provided on the significance and nutritional properties of peach and carrot fruits used as the basis for the development of the drink. The data characterizing the quality of the pectin extract obtained from grape products and used in the technology of the drink as an enriching component and having detoxifying properties are presented.  A comparative tasting evaluation of the experimental samples of the drink is given; on its basis the optimal formulation for the production of an enriched beverage with pronounced detoxification and adaptogenic properties is determined. Particular attention is paid to studies confirming the nutritional and biological value of the developed drink. The detoxifying properties of the drink are confirmed by studies to determine its complexing ability. It has been found that 1 g of pectin contained in the drink is able to bind and remove 151.7 ml of lead from the human body.  The presented studies allow one to obtain high-quality drinks based on natural raw materials, to expand the range of preventive products that can eliminate the shortage of necessary nutrients for humans.